The Effectiveness of Hanging Ornamental Plants in Absorbing solar Radiation for Enviromental Temperature Control - Harmin, Amalia; Muhammad Isra; Fauzan; Marini Bravikawati; Sarah Niaci; Afrahun Naziah; Bukhari Kasim; Akbar Rizqullah (E-Journal Universitas Malikussaleh, 2025)
Global climate change, characterized by an increase in the average temperature of the Earth, is an important issue that affects human life. One of the phenomena that occurs is the Urban Heat Island (UHI) phenomenon. This phenomenon occurs due to the lack of green plants that function as absorbers of solar heat. However, the effectiveness of plants in absorbing solar heat can vary. Therefore, experimental scientific studies are needed to determine the extent to which hanging ornamental plants can absorb solar heat. This study tested five types of hanging ornamental plants to obtain heat absorption values, namely Epipremnum aureum, Chlorophytum comosum, Paperomia hopei, Discidia geri, and Tradescantia spatcheae. The results of the study found that Chlorophytum Comosum (spider plant) had the highest heat absorption value of 1 kJ. This study contributes to providing solutions for controlling environmental temperature.